New DAG and cAMP Sensors Optimized for Live-Cell Assays in Automated Laboratories - Tewson, Paul H.; Martinka, Scott; Shaner, Nathan C.; Hughes, Thomas E.; Quinn, Anne Marie (Journal of biomolecular screening, 2016)
Protein-based, fluorescent biosensors power basic research on cell signaling in health and disease, but their use in automated laboratories is limited. We have now created two live-cell assays, one for diacyl glycerol and another for cAMP, that are robust (Z′ > 0.7) and easily deployed on standard fluorescence plate readers. We describe the development of these assays, focusing on the parameters that were critical for optimization, in the hopes that the lessons learned can be generalized to the development of new biosensor-based assays.